Penggunaan Teknologi Kesehatan dalam Mendukung Manajemen Kesehatan Anak setelah Menjalani Perawatan - Friska Nababan; Siti Chodijah; Dessie Wanda (Journal of Telenursing (JOTING), 2023)
This study aims to discover how health technology-based applications support managing children's health, whether carried out by the patients themselves or their parents. The method used is a systematic review by searching articles through online databases, including PubMed, Science Direct, Ebsco, Sage Publication, Cochrane Library-Cochrane Reviews, Embase, CINAHL, and Clinical Key Nursing. The results showed that using health technology-based applications affected increasing self-confidence, controlling disease conditions, competency and knowledge levels, parental self-efficacy in caring for children, increasing medication adherence, and improving children's quality of life. Apart from that, the effectiveness of time and materials also has a positive impact on the use of health technology. In conclusion, health technology-based applications provide a positive influence or effect that supports parents (caregivers) in managing their children's health well. Increasing parents' self-confidence, self-efficacy, knowledge, and competence in caring for children will accelerate parents' transition to caring for children at home. Keywords: Mobile Application, Home Care, Child Health Management, Health Technology